Performance of the OptiMAL® dipstick in the diagnosis of malaria infection in pregnancy - Harry Tagbor; Jane Bruce; Edmund Browne; Brian Greenwood; Daniel Chandramohan (Dove Medical Press, 2008)
Harry Tagbor1, Jane Bruce2, Edmund Browne1, Brian Greenwood2, Daniel Chandramohan21Department of Community Health, School of Medical Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana; 2Department of Infectious and Tropical Diseases, London School of Hygiene and Tropical Medicine, London, UKAbstract: The accuracy of OptiMAL® dipsticks was compared with that of microscopy in the diagnosis of malaria infection in pregnancy. During the course of a clinical trial of antimalarial drugs in pregnancy, we screened 4500 pregnant women of all parities who accessed antenatal clinic services at St. Theresa’s Hospital’s in Nkoranza, Ghana, between March 2003 and December 2004 with OptiMAL® dipsticks and confi rmed the diagnosis of malaria with microscopy. We determined the sensitivity, specificity, positive and negative predictive values, and the area under receiver operating characteristic (ROC) curve for the OptiMAL® antigen test compared to microscopy for the diagnosis of malaria infection in pregnancy. OptiMAL® dipsticks had a sensitivity of 96.6%, specificity of 85.4%, a positive predictive value of 92.7%, a negative predictive value of 92.6%, and an area under the ROC curve of 0.91 (95% CI of 0.90–0.92). The diagnostic accuracy of the OptiMAL® dipstick is high and the test may have practical use in the diagnosis of malaria infection in pregnancy in malaria endemic countries.Keywords: malaria, diagnosis, pregnancy, OptiMAL dipstick, microscopy